Effects of an educational program in increasing knowledge and reducing premenstrual syndrome signs, symptoms and severity among nursing college students - Abdalla, Nafisa; Gibreel, Mohammed (International Journal of Basic and Applied Sciences, 2016)
Objective: The objective of the following study is to determine the effects of an Educational Program in increasing knowledge and reducing premenstrual syndrome symptoms and severity among nursing college students.Material and Methods: A total of 60 students with Premenstrual Syndrome (PMS) symptoms were included in the study group (n=60), the age of the majority of them (75.8%) was between 20-24 years, pre and post education program questionnaire was developed as a tool of data collection before and after the educational program. Also premenstrual symptoms and severity follow-up sheet was designed and conducted three month after the post education program to follow the effectiveness of the educational program in reducing the severity of the symptoms.Results: The study results indicate that there was significant difference between students’ knowledge before and after the program, the total score mean rank before program was (34.72), while after program was (86.28) p < 0.01 with significant difference between score before and after the program at 1% level of significant. It also shows a significant difference between PMS signs, symptoms and severity before and after program at 1% level of significant (total score mean and SD before program were (132.42, 13.72) respectively, and after program are (107.52, 14.47) respectively p < 0.01 with larger effect size of 0.613. The follow-up result shows a reduction in PMS symptom’s severity, the total severity averages of PMS sign and symptoms were 3.4 first month, 2.6 the second month and 2.2 for the third month out of 4 respectively.Conclusion: The educational program had a positive effect on increasing knowledge and decreasing PMS signs and symptoms severity. Also the program has decrease the effect of PMS signs and symptoms on study group life.
Keywords: Premenstrual Syndrome; Knowledge; Signs; Symptoms; Severity; Educational Program.